Monocytes serve as Shiga toxin carriers during the development of hemolytic uremic syndrome - Xinlei Sun; Shuang Qu; Fenglian Zhou; Fujie Shi; Yunfei Wu; Lin Gu; Minghui Liu; Zhen Bian; Lei Shi; Zhihong Liu; Yuan Liu; Ke Zen (Cellular & Molecular Biology Letters)
Abstract Shiga toxin (Stx)-induced hemolytic uremic syndrome (HUS) poses a life-threatening complication for which a definitive treatment remains elusive. To exert its cytotoxic effect on renal cells, Stx must be delivered from the infected intestines to the kidney. However, the mechanism underlying Stx delivery remains unclear. Here we pinpoint monocytes as the primary carriers responsible for transporting Stx2 to the renal region. Through single-cell sequencing analysis of Stx2-B-bound peripheral white blood cells sorted by flow cytometry, we observe that nearly all monocytes exhibit strong Stx2-B binding, whereas less than 10% of neutrophils are associated with Stx2-B, albeit with a lower affinity. Further examination of the single-cell dataset and cell binding assays suggest that monocytes likely bind to Stx2-B through the Toll-like receptor 4. Remarkably, Stx-laden monocytes demonstrate their ability to transport Stx2 to human renal glomerular endothelial cells (HRGEC), subsequently inducing apoptosis in HRGEC. In a mouse model of Stx1/2-positive EDL933 infection-induced HUS, the presence of Stx2-positive monocytes in peripheral blood and infiltrated kidney tissues was observed. Finally, depleting monocytes through the usage of a CD14 neutralizing antibody or blocking monocyte chemotaxis via inhibition of CCL2 notably mitigates kidney injury and dysfunction caused by lipopolysaccharide (LPS)/Stx2 treatment. Our findings unveil the pivotal role of monocytes in Stx delivery during STEC infection and offer a promising therapeutic approach for Stx-induced HUS.